Extensive Reading of Children's Literature in First, Second, and Foreign Language Vocabulary Acquisition - Dominic Cheetham (CLELEjournal, 2015)
Extensive reading of children's literature can be seen as one of the most powerful means to acquiring a large working vocabulary for both first language learners and second language learners. However, for foreign language learners, children's literature has a less positive image. For foreign language learners the most commonly recommended reading is of graded readers. Corpus research has shown that work for children has a wide range of rare words, comparable to adult literature, and this leads to the argument that children's literature puts too great a comprehension and memory strain on foreign language learners, and is an inefficient learning tool compared to graded readers. This paper reviews existing research and examines the arguments for children's literature in language learning in terms of some features of naturalistic child reading behaviour, and the stylistic choices of writers for children. Replication of child reading behaviours in conjunction with the aid to comprehension and memory inherent in stylistic choices, combined with motivational and practical considerations, are argued to make children's literature an equal, if not superior choice as extended reading material for foreign language learners.